Descriptive Characteristics and Outcomes of Patients Undergoing Revision Anterior Cruciate Ligament Reconstruction With and Without Tunnel Bone Grafting. Issue 9 (July 2022) - ; DeFroda, Steven F.; Owens, Brett D.; Wright, Rick W.; Huston, Laura J.; Pennings, Jacquelyn S.; Haas, Amanda K.; Allen, Christina R.; Cooper, Daniel E.; DeBerardino, Thomas M.; Dunn, Warren R.; Lantz, Brett Brick A.; et al.
Background: Lytic or malpositioned tunnels may require bone grafting during revision anterior cruciate ligament reconstruction (rACLR) surgery. Patient characteristics and effects of grafting on outcomes after rACLR are not well described. Purpose: To describe preoperative characteristics, intraoperative findings, and 2-year outcomes for patients with rACLR undergoing bone grafting procedures compared with patients with rACLR without grafting. Study Design: Cohort study; Level of evidence, 3. Methods: A total of 1234 patients who underwent rACLR were prospectively enrolled between 2006 and 2011. Baseline revision and 2-year characteristics, surgical technique, pathology, treatment, and patient-reported outcome instruments (International Knee Documentation Committee [IKDC], Knee injury and Osteoarthritis Outcome Score [KOOS], Western Ontario and McMaster Universities Osteoarthritis Index, and Marx Activity Rating Scale [Marx]) were collected, as well as subsequent surgery information, if applicable. The chi-square and analysis of variance tests were used to compare group characteristics. Results: A total of 159 patients (13%) underwent tunnel grafting—64 (5%) patients underwent 1-stage and 95 (8%) underwent 2-stage grafting. Grafting was isolated to the femur in 31 (2.5%) patients, the tibia in 40 (3%) patients, and combined in 88 patients (7%). Baseline KOOS Quality of Life (QoL) and Marx activity scores were significantly lower in the 2-stage group compared with the no bone grafting group ( P ≤ .001). Patients who required 2-stage grafting had more previous ACLRs ( P < .001) and were less likely to have received a bone–patellar tendon–bone or a soft tissue autograft at primary ACLR procedure ( P ≤ .021) compared with the no bone grafting group. For current rACLR, patients undergoing either 1-stage or 2-stage bone grafting were more likely to receive a bone–patellar tendon–bone allograft ( P ≤ .008) and less likely to receive a soft tissue autograft ( P ≤ .003) compared with the no bone grafting group. At 2-year follow-up of 1052 (85%) patients, we found inferior outcomes in the 2-stage bone grafting group (IKDC score = 68; KOOS QoL score = 44; KOOS Sport/Recreation score = 65; and Marx activity score = 3) compared with the no bone grafting group (IKDC score = 77; KOOS QoL score = 63; KOOS Sport/Recreation score = 75; and Marx activity score = 7) ( P ≤ .01). The 1-stage bone graft group did not significantly differ compared with the no bone grafting group. Conclusion: Tunnel bone grafting was performed in 13% of our rACLR cohort, with 8% undergoing 2-stage surgery. Patients treated with 2-stage grafting had inferior baseline and 2-year patient-reported outcomes and activity levels compared with patients not undergoing bone grafting. Patients treated with 1-stage grafting had similar baseline and 2-year patient-reported outcomes and activity levels compared with patients not undergoing bone grafting.